Two new species of comb-clawed beetles (Coleoptera: Tenebrionidae: Alleculinae) from Yunnan, China - Li, Zhaoxu; Ren, Guodong (Zootaxa, 2019)
Two new alleculine species, Bobina cuspidenta sp. nov. and Loricula unidentata sp. nov., are described and illustrated from Yunnan, China. Keys to the species of the genera Bobina and Loricula are also given.